Pemanfaatan Tepung Biji Durian Dalam Pembuatan Kulit Choux Paste - Vinka Conia; Lilis Sulandari; Mauren Gita Miranti; Niken Purwidiani (Concept: Journal of Social Humanities and Education, 2024)
The main raw material commonly used in making choux paste skin is wheat flour. The wheat flour used is high protein wheat flour. High protein wheat flour has a protein content of 14.45%, fiber 2.01%, and carbohydrates in the form of starch 78.36% (Industrial Research and Consultation Center, 2016). The amylose and amylopectin content in high protein wheat flour is 50.26% and 22.84% (Industrial Research and Consultation Center, 2016). Amylose plays a role in forming gel while amylopectin forms elastic properties. The formation of the dough framework can occur due to the gelatinization ability of starch when the dough is baked. To reduce dependence on the use of wheat flour in making choux paste skin, it can be overcome by increasing the use of local food ingredients, in accordance with Law Number 18 Article 1 Paragraph 16 of 2012 concerning Food of the Republic of Indonesia (UU No. 18/2012), "Food diversity is an effort increasing the availability and consumption of food that is diverse, nutritionally balanced and based on local resource potential."